Phân tích các đa thức thành nhân tử: `a) x^3 + 2x^2 + 2x +1` `b) x^4 + 2x^3 -4x -4` `c) x^3 – 7x -6`

Phân tích các đa thức thành nhân tử:
`a) x^3 + 2x^2 + 2x +1`
`b) x^4 + 2x^3 -4x -4`
`c) x^3 – 7x -6`

2 bình luận về “Phân tích các đa thức thành nhân tử: `a) x^3 + 2x^2 + 2x +1` `b) x^4 + 2x^3 -4x -4` `c) x^3 – 7x -6`”

  1. a) x3 + 2x2 – 2x -1
    = x^3 – x^2 + 3x^2 – 3x + x – 1
    = (x – 1)(x^2 + 3x + 1)
    b) x^4 + 2x^3 – 4x – 4
    = (x^2 – 2)(x^2 + 2) + 2x(x^2 – 2)
    = (x^2 – 2)(x^2 + 2x + 2)
    c) x^3 – 7x + 6
    = x^3 – x^2 + x^2 – x – 6x + 6
    = x^2(x – 1) + x(x – 1) – 6(x – 1)
    = (x – 1)(x^2 + x – 6)
    = (x – 1)(x^2 + 3x – 2x – 6)
    = (x – 1)[x(x + 3) – 2(x + 3)]
    = (x – 1)(x + 3)(x – 2)

    Trả lời
  2. $a)x^3+2x^2+2x+1$
    $=(x^3+x^2+x)+(x^2+x+1)$
    $=x(x^2+x+1)+(x^2+x+1)$
    $=(x^2+x+1)(x+1)$
    $b)x^4+2x^3-4x-4$
    $=(x^4+2x^3+x^2)-(x^2+4x+4)$
    $=x^2(x+1)^2-(x-2)^2$
    $=(x(x+1)-x+2)(x(x+1)+x-2)$
    $=(x^2+2)(x^2+2x-2)$
    $c)x^3-7x-6$
    $=x^3-3x^2+3x^2-9x+2x-6$
    $=x^2(x-3)+3x(x-3)+2(x-3)$
    $=(x-3)(x^2+3x+2)$
    $=(x-3)(x^2+x+2x+2)$
    $=(x-3)(x(x+1)+2(x+1))$
    $=(x-3)(x+1)(x+2)$
    Chúc bạn học tốt !!!!!
     

    Trả lời

Viết một bình luận

Câu hỏi mới